Conversational synchrony in the communicative interactions of individuals with traumatic brain injury - Gordon, Rupa Gupta (Brain Inj, 2015)
PRIMARY OBJECTIVE: To assess conversational synchrony in moderate to severe traumatic brain injury (TBI). Conversational synchrony, assessed by the similarity and coordination of words and words per turn, allows for effective and efficient communication and enhances the development of rapport. RESEARCH DESIGN: Eighteen participants with TBI (7 females) and nineteen healthy comparison participants (CP; 8 females) engaged in a 10-minute conversation with an unfamiliar partner. METHODS AND PROCEDURES: Conversational synchrony was assessed in these conversations by measuring the degree to which the participants’ productions of words and words per turn became more similar to one another over the course of the session MAIN OUTCOMES AND RESULTS: Significantly more sessions with participants with TBI (11/18 for words, 9/18 for words per turn) compared to CP sessions (5/19 for words, 4/19 for words per turns) did not display conversational synchrony. Likewise, synchrony was significantly correlated with subjective ratings of the interaction from raters who were blind to participant status and the study hypotheses. CONCLUSIONS: These results suggest that TBI can disrupt conversational synchrony and can, in turn, negatively impact social perceptions. The relationship between impaired conversational synchrony and other social communicative deficits in TBI warrants further study.